Pengembangan Multimedia Interaktif Berbasis Aplikasi Superzat pada Siswa Kelas IV di SDN Sidodadi 1/153 Surabaya - Yossy Novita Surya Rahmawati; Ika Dian Rahmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by students' low understanding and learning outcomes in the topic of the states of matter and their changes, which were attributed to teacher-centered instruction dominated by lecture methods and the limited use of technology-based interactive learning media. As a result, students tended to be less actively engaged and easily became bored during the learning process. This study aimed to develop Superzat, an application-based interactive multimedia learning medium that is valid, effective, and practical. The study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The development process included: (1) analysis of learning outcomes, student characteristics, and learning media needs; (2) design of the multimedia product; (3) development of the product followed by expert validation and empirical validation of the test instruments. The validation results showed scores of 81% from the media expert, 89% from the subject matter expert, 90% from the instructional design expert, and 93% from the language expert, indicating that the product was highly feasible. During the implementation stage, the multimedia was evaluated for its effectiveness and practicality. The results showed that teacher activity reached 100%, while student activity reached 95.87%. In addition, the Superzat interactive multimedia was categorized as highly practical, with teacher and student response rates of 96.25% and 93.33%, respectively. The improvement in students' learning outcomes was demonstrated by an average N-Gain score of 87%, which falls into the high category. Therefore, the Superzat application-based interactive multimedia is considered suitable for use as an elementary science (IPAS) learning medium for teaching the topic of the states of matter and their changes.